The role of ordinary production associations of the peasantry and cossacks in the restoration of agriculture in the North Caucasus (1921– 1924) - A. A. Panarin (Гуманитарные и юридические исследования)
The article examines the process of creation and development of the simplest production associations of the peasantry and Cossacks in the North Caucasus in 1921- 1924. The problem posed is relevant from the point of view of using historical experience to improve the organization of agricultural production in modern Russia. The state of agriculture in the region after the end of the Civil War is analyzed. The extreme decline of agriculture and animal husbandry is emphasized, information is provided on a significant reduction in means of production and human resources. The negative impact of the food policy pursued by the Soviet state in the early 1920s, which hindered the development of agriculture, is noted. The measures taken by the party and state bodies to create production associations of the peasantry are highlighted. The characteristic of the socalled supryage is given and its significance in the struggle for the expansion of the sown area is revealed. The role of seed farms in the cultivation of pure grain is revealed. The activityof reclamation associations is considered, their importance in the development of irrigation and water protection systems is noted. The development of livestock associations is analyzed, examples of their effective activities in increasing the number of livestock and improving its quality characteristics are given. There is a weak development of machine partnerships in the early 1920s. The positive results of the participation of the simplest production associations of the peasantry and Cossacks in the restoration and development of agriculture in the North Caucasus are emphasized.